Suitable solvent of a new copolymer as a pre-investigation of its static laser scattering - Ghazy, Riyad (2008)
Summary: An interferometric method, Mach-Zehnder interferometer, is applied to determine both refractive index and refractive index increments (dn/dc) for a new copolymer material poly-(4-vinylphenol-co-2-hydroxethyl methacrylate), PVPh-HEM, in different solvents like methanol and dimethylformamide. The PVPh-HEM is solved in each solvent with different concentrations ranging from 0.004 to 0.010 g/ml. The light source we have used is the argon-ion laser with the wavelength of 488 nm. This work is carried out as a step for the determination of the average molecular weight of PVPh-HEM and its other related scattering parameters
Bibliografija: 16 jed
Sažetak
Keywords: Polimeri -- Optička svojstva; Polimeri -- Spektroskopija